Democratizing Data Analytics: Lightweight AI Solutions to Improve Operational Efficiency in SMEs - Liu, Zhijun (European Journal of AI, Computing & Informatics, 2026)
Small and medium-sized enterprises (SMEs) generate significant amounts of operational data, yet often lack the resources and technical expertise to transform this data into actionable insights. Traditional data analytics solutions are frequently too complex, costly, or resource-intensive for SMEs, limiting their ability to leverage data effectively. This paper explores the role of lightweight artificial intelligence (AI) in democratizing data analytics and enhancing operational efficiency within SMEs. Lightweight AI solutions are characterized by ease of deployment, low technical barriers, and a focus on practical, high-impact applications. They enable SMEs to optimize business processes, gain insights into customer behavior, and improve resource allocation without requiring substantial infrastructure or specialized personnel. Implementation considerations include clearly defining business objectives, adopting incremental pilot projects, engaging employees, and maintaining transparency and human oversight in interpreting analytical outputs. While limitations such as data quality, resource constraints, and the potential for overreliance on automated recommendations exist, SMEs can mitigate these challenges through careful planning, iterative adoption, and flexible decision-making. Looking forward, lightweight AI has the potential to integrate progressively into SME operations, fostering a culture of data-driven decision-making and enabling organizations to respond more effectively to dynamic business environments. By leveraging accessible AI tools, SMEs can enhance efficiency, improve operational resilience, and build sustainable competitive advantages.